THE EFFECT OF FINANCIAL LITERACY, FINANCIAL INCLUSION AND INFORMATION TECHNOLOGY ON THE FINANCIAL PERFORMANCE OF SMEs, BEKASI REGENCY - Sesri Sellina; Etty Zuliawati Zed (SEAN Institute, 2023)
This study aims to examine and analyze: (1) the effect of financial literacy on financial performance, (2) the effect of financial inclusion on financial performance and (3) the effect of information technology on financial performance. The population in this study are all MSME actors in Bekasi Regency that we can reach. In this study, the samples obtained were 230 respondents obtained using the convenience sampling method. This study uses primary data by distributing questionnaires. The analytical method used in this research is multiple linear regression analysis using the t-test hypothesis test. The test results prove that the variables of financial literacy, financial inclusion and information technology have an effect on the financial performance of MSMEs. The effect of the independent variable on the dependent variable is 59.75%, while the remaining 40.25% is influenced by other factors not examined in this study.